Challenges of professional teaching initiation in early childhood education - Perondi, Marisete Maihack (2021)
Thus, in this work, we aim to identify and analyze the challenges at the beginning of the teaching career in early childhood education of teachers in a town in the west of Santa Catarina. We had as collaborators six teachers with until five years of teaching experience who were interviewed. The study adopted a qualitative approach and the data were worked through the content analysis. We identified that the beginning of a teaching career in early childhood education was marked by different challenges, by different orders such as, for example, insecurity, the unknown, large classes, the lack of teaching materials, responsibility for learning, and planning of practices. The identified challenges were classified into common challenges to teachers independent of their career stages, common challenges to beginning teachers, and specific challenges of beginning teachers in early childhood education. Among the latter are the knowledge of the specifics of the children’s age groups, the establishment of the school routine with the children, the recognition and relationship with parents, and the identity transition from teaching assistant to the teacher. So that the strategies to overcome these challenges are not based only on the beginning teachers themselves and on their teaching experiences, we suggest that, among others, early childhood education institutions and their professionals welcome and support them, providing opportunities for dialogue, listening attentively and sharing practices and experiences.